The Consumption of Wild Edible Plants - Carvalho, Ana Maria (2018)
Wild edible plants are of great importance in both former and current human societies. Their use embodies evolutionary trends, continuing interactions between men and nature, relevant traditional knowledge, and cultural heritage. A conceptual approach to wild edible plants, including the contribution of such species to people's diets and daily lives, focusing on nutritional and cultural value, food sovereignty and security, as well as the huge legacy for future generations, leads to a general overview of new tendencies and availability of wild plant resources according to geographic regions. The potential benefits and the continual need for conservation strategies of plants, habitats, and associated knowledge are also discussed, enhancing biodiversity and biocultural patrimony. Finally, some examples of culturally significant edible wild plants are described, emphasizing the importance of knowledge transmission and sustainable uses in a changing world.